不显含y型,记y'=p,则y"=dp/dx=p',
(1-x^2)y"-xy'=2原微分方程可化为
(1-x^2)p'-xp=2
p'-x/(1-x^2)p=2/(1-x^2)
公式法得
p=[e^(∫x/(1-x^2)dx][C1+∫2/(1-x^2)[e^(∫-x/(1-x^2)dx]dx]
=e^(-1/2)ln(1-x^2)[C1+∫{2/(1-x^2)e^[(1/2)ln(1-x^2)]}dx]
=(1-x^2)^(-1/2)[C1+∫{[2/(1-x^2)](1-x^2)^(1/2)}dx]
=(1-x^2)^(-1/2)[C1+∫{[2/(1-x^2)]^(1/2)dx]
=(1-x^2)^(-1/2)[C1+2arcsinx]
即dy/dx=(1-x^2)^(-1/2)[C1+2arcsinx]
∫dy=∫(1-x^2)^(-1/2)[C1+2arcsinx]dx
y=(1/2)∫[C1+2arcsinx]d(C1+2arcsinx)
得y=(1/4)(C1+2arcsinx)^2+C2
特征方程 4r^2+4r+1=0 (2r+1)=0 r1=r2=-1/2
所以 通解为(c1+c2x)e^(-1/2x)
y"-4y'+13y=0
r^2-4r+13=0
deta